Angiosarcoma of the Face: A Case Study and Literature Review of Local and Metastatic Angiosarcoma - Hugo Lara-Martinez; Molly Weinberg; Praneeth Baratam; Jeffrey Horn; Kristine Ward; Michael Styler (Case Reports in Oncological Medicine)
Angiosarcomas are vascular malignancies with a tendency to spread extensively both locally and systemically. We report a case of cutaneous angiosarcoma of the face in a 53-year-old man that was originally misdiagnosed as an abscess. Initially small, the lesion enlarged over a four-to-six-month period and began to bleed. Two shave biopsies were performed that returned a diagnosis of angiosarcoma. The patient underwent radical resection and lymph node dissection, which revealed positive margins and ten of forty-six positive lymph nodes. The patient was treated with paclitaxel and concurrent radiation therapy (RT). Restaging scans showed a new sclerotic lesion of the T10 vertebra, three hepatic lesions, and an adrenal lesion, all concerning for metastasis. Biopsy of one of the hepatic lesions was consistent with metastatic angiosarcoma. In this review, we discuss the presentation of cutaneous angiosarcoma, the importance of early diagnosis, and the treatment options available for metastatic disease that has failed first-line chemotherapy.